Prognostic Impact of QRS Axis Deviation in Patients Treated With Cardiac Resynchronization Therapy. (14th January 2016) - PERROTTA, LAURA; KANDALA, JAGDESH; DI BIASE, LUIGI; VALLEGGI, ALESSANDRO; MICHELOTTI, FEDERICA; PIERAGNOLI, PAOLO; RICCIARDI, GIUSEPPE; MASCIOLI, GIOSUÈ; LAKKIREDDY, DHANUNJAYA; PILLARISETTI, JAYASREE; EMDIN, MICHELE; NATALE, ANDREA; et al.
Prognosis of QRS Axis Deviation in CRT‐D: Introduction: QRS duration and morphology are currently recognized as recommended criteria for the selection of CRT candidates. It has recently been shown that patients with left bundle branch block (LBBB) derive substantial clinical benefit from CRT. The aim of this study is to investigate the prognostic impact of QRS axis deviation (AD) in HF patients with LBBB undergoing CRT. Methods and Results: We retrospectively evaluated 707 HF patients with LBBB who underwent CRT at five centers. Baseline QRS axis was defined as normal (NA: –30° to 90°), right axis deviation (RAD: 90° to 180°) and left axis deviation (LAD: <−30°). The primary endpoint was a composite of all cause death/HF hospitalization. The risk of endpoint by AD was evaluated with both Kaplan–Meier and Cox proportional hazard analysis. Among 707 patients (73% M, median age: 71 [62, 77] years), 323 (46%) had NA, 359 (51%) LAD, and 25 (3.5%) RAD. Baseline clinical characteristics were similar between the three groups. Over a mean follow‐up of 32 ± 25 months, 141 deaths occurred (21%) and 36% (n = 255) met with the composite endpoint. A significantly higher proportion of RAD patients (52%) reached the endpoint (LAD 40%, NA 30%). KM analysis showed that RAD and LAD patients had worse event free survival and in multivariate analysis both LAD (HR: 1.40; 95% CI: 1.05–1.86; P = 0.021) and RAD (HR: 2.49; 95% CI: 1.31–4.74; P = 0.005) were independently associated with worse clinical outcome. Conclusions: Right or left axis deviation in the presence of LBBB in HF patients undergoing CRT are independent predictors of poor prognosis.